Teknik Pelayanan Perpustakaan Untuk Pembaca - Fitry, Susanti Arian (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Library management has experienced rapid development as a result of developments in information technology where conventional or manual library management has developed into information technology-based management known as library automation. The use of information technology in libraries is not only limited to routine library work such as processing, browsing and circulating collections but also to providing on-line learning resources in various forms of media, searching and downloading digital information across libraries quickly and accurately, and utilizing networks. internet for information processing in the context of research and development of science and technology. The introduction of computers into libraries has changed the face of libraries, from libraries that provide services manually to automated libraries, from libraries limited by walls and rooms to unlimited libraries equipped with electronic means to access information in various formats and from various sources. information around the world. In this paper, researchers use a descriptive qualitative approach with the main source of data being written data related to library management. The research results show that two important things are the focus of modern libraries today, namely user satisfaction and the use of information technology for management and improving library performance. The use of information technology is expected to improve library performance and increase user satisfaction. Library management must be carried out well and systematically so that the services provided are in accordance with the needs of its users. There are 3 (three) service systems that can be implemented in libraries, namely open service systems, closed service systems and mixed service systems. The implementation of the service system is adjusted to the situation and conditions of each library by taking into account the principles of library services.